2018
DOI: 10.1002/stem.2894
|View full text |Cite
|
Sign up to set email alerts
|

P2X7 Receptors Regulate Phagocytosis and Proliferation in Adult Hippocampal and SVZ Neural Progenitor Cells: Implications for Inflammation in Neurogenesis

Abstract: Identifying the signaling mechanisms that regulate adult neurogenesis is essential to understanding how the brain may respond to neuro-inflammatory events. P2X7 receptors can regulate pro-inflammatory responses, and in addition to their role as cation channels they can trigger cell death and mediate phagocytosis. How P2X7 receptors may regulate adult neurogenesis is currently unclear. Here, neural progenitor cells (NPCs) derived from adult murine hippocampal subgranular (SGZ) and cerebral subventricular (SVZ) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 70 publications
1
30
0
Order By: Relevance
“…While P2X7-dependent calcium increase is not surprising in case of C6 cells (Wei et al, 2008), to our knowledge there are no reports specifically describing presence or absence of P2X7-initiated calcium influx in the two human glioma cell lines. However, P2X7-mediated calcium signals were observed in human astrocytes, murine neural progenitor cells and rat oligodendrocyte precursor cells and all these cell types are top candidates to be the putative cells of origin for glioma (Alloisio et al, 2006;Narcisse et al, 2005;Jiang & Uhrbom, 2012;Wang et al, 2009;Leeson et al, 2018). The detailed nature of the observed signal is however not exactly clear since there are strong proofs for its metabotropic character (Supłat-Wypych et al, 2010) as well as suggestions of active ATP release through P2X7 receptors (Brandao-Burch et al, 2012).…”
Section: Calcium Influx and Large Pore Formation Upon P2x7 Stimulationmentioning
confidence: 99%
“…While P2X7-dependent calcium increase is not surprising in case of C6 cells (Wei et al, 2008), to our knowledge there are no reports specifically describing presence or absence of P2X7-initiated calcium influx in the two human glioma cell lines. However, P2X7-mediated calcium signals were observed in human astrocytes, murine neural progenitor cells and rat oligodendrocyte precursor cells and all these cell types are top candidates to be the putative cells of origin for glioma (Alloisio et al, 2006;Narcisse et al, 2005;Jiang & Uhrbom, 2012;Wang et al, 2009;Leeson et al, 2018). The detailed nature of the observed signal is however not exactly clear since there are strong proofs for its metabotropic character (Supłat-Wypych et al, 2010) as well as suggestions of active ATP release through P2X7 receptors (Brandao-Burch et al, 2012).…”
Section: Calcium Influx and Large Pore Formation Upon P2x7 Stimulationmentioning
confidence: 99%
“…Emerging evidence, both functional and genetic, now points to an important scavenger role of an archaic purinergic receptor, P2X7, within the CNS in which P2X7 was found expressed in brain macrophages, microglia, astrocytes, oligodendrocytes, new born rat and human embryonic brain neurones but not adult cortical neurones (Collo et al, 1997;Sim et al, 2004;Hamilton et al, 2009;Lovelace et al, 2015;Yamamoto et al, 2013). A recent study using wild-type and P2X7 À/À C57BL/6 mice demonstrated the expression of the P2X7 receptor on neural progenitor cells isolated from hippocampal subgranular and cerebral subventricular zones (Leeson et al, 2018). Most published studies of P2X7 receptors have focused on the pro-inflammatory 'pore' function of this receptor, but the requirement for high concentrations (>100 μM, but usually 1-5 mM depending on ambient divalent cations) of extracellular ATP for pore opening would be rarely achieved in physiological conditions, suggesting that this receptor has an alternative non-inflammatory function in the CNS.…”
Section: Introductionmentioning
confidence: 99%
“…Extracellular nucleotides mediate their effects through metabotropic G-protein-coupled P2Y purinergic receptors and ionotropic purinergic P2X receptors, both of which are expressed in the V-SVZ and induce Ca 2+ transients (Stafford et al, 2007;Messemer et al, 2013). Specifically, the P2X7R subtype that has been detected in ependymal (E) is also expressed in transient amplifying progenitors (C cells) where it plays a dual role: in the absence of the ligand, P2X7R functions as a scavenger receptor involved in phagocytosis and following its activation by ATP, the P2X7R reduces proliferation of C cells (Genzen et al, 2009;Messemer et al, 2013;Leeson et al, 2018). It should be mentioned here that although these data appear contradictory with the fact that increased levels of extracellular nucleotides favor cell proliferation, ATP also acts on other receptors among which the metabotropic P2Y1R receptors that foster expansion of the C cell population (Suyama et al, 2012).…”
Section: Ligand-gated Ion Channels (Lgics)mentioning
confidence: 99%